2013
DOI: 10.1159/000350859
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy in Elderly Patients with Gynecological Cancer

Abstract: Objective: The aim of this study was to determine the tolerability, safety and feasibility of chemotherapy in very elderly patients with gynecological cancers. Methods: We included all patients ≥75 years of age affected by endometrial, ovarian or cervical cancer treated with neoadjuvant, adjuvant or palliative chemotherapy. Data regarding age, stage of the disease, comorbidities, performance status (PS), chemotherapy regimen and dosing, toxicity, treatment delay and dose adjustments were recorded. Results: For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
1
6
0
1
Order By: Relevance
“…This demonstrates that standard doublet therapy is feasible and tolerable in the majority of elderly patients. This corroborates previously published series, which showed 65-77% completion rate for patients over age 65 [20,33].…”
Section: Discussionsupporting
confidence: 93%
“…This demonstrates that standard doublet therapy is feasible and tolerable in the majority of elderly patients. This corroborates previously published series, which showed 65-77% completion rate for patients over age 65 [20,33].…”
Section: Discussionsupporting
confidence: 93%
“…[8] Palaia et al in his audit of elderly patients also concluded that elderly patients receiving weekly therapy tolerated it better. [15] Similarly, in MITO-7 study, weekly paclitaxel and carboplatin adjuvant schedule was better tolerated, with a lower level of hematological toxicity, particularly febrile neutropenia, than the 3 weekly schedule. [16] The regimen had a response rate of 100%, with 27.27% of patients having a complete response.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies have shown that chemotherapy and radiotherapy can be well tolerated in this population. 18,19 However, patient motivators and quality of life must be evaluated alongside safety and efficacy when considering adjuvant therapy recommendations in the elderly population. In addition, providers should further investigate barriers that prevent elderly women from receiving guideline directed care.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that further evaluation of the physical and psychological role of chemotherapy on quality of life would be warranted. 18 Similarly, multiple providers have found radiation to be safe in elderly patients with EC. 13,19Y21 Fiorentino et al 19 found that adjuvant external beam radiation followed by brachytherapy in elderly patients with EC not only had an acceptable safety profile but also was well tolerated regardless of pre-existing medical comorbidities.…”
mentioning
confidence: 99%